2006
DOI: 10.1176/foc.4.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Consultation: A Model of Mental Health Service for Multicultural Societies

Abstract: C ulture shapes the experience and expression of emotional distress and social problems in myriad ways (1,2). To accurately diagnose and treat patients from diverse back

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(115 citation statements)
references
References 32 publications
(12 reference statements)
0
113
0
2
Order By: Relevance
“…133 Given the CCB's wide jurisdiction and its use of a "color-blind" Similar to the theoretical underpinnings of this study, the CRPD appears to be endorsing the social model of disability and an intersectional approach to understanding the realities faced by persons with disabilities. 135 For instance, the preamble of the CRPD states "that disability results from the interaction between persons with impairments and attitudinal and environmental barriers that hinders their full and effective participation in society on an equal basis with others" 136 It also recognizes "difficult conditions faced by persons with disabilities who are subject to multiple or aggravated forms of discrimination on the basis of race, colour, sex, language, religion, political or other opinion, national, ethnic, indigenous or social origin, property, birth, age or other <http://www.un.org/disabilities/default.asp?id=17>. Also, in regard to Article 12 (4), Canada reserves the right not to subject all such measures to regular review by an independent authority, where such measures are already subject to review or appeal.…”
Section: United Nations Convention On the Rights Of Persons With Disamentioning
confidence: 99%
See 1 more Smart Citation
“…133 Given the CCB's wide jurisdiction and its use of a "color-blind" Similar to the theoretical underpinnings of this study, the CRPD appears to be endorsing the social model of disability and an intersectional approach to understanding the realities faced by persons with disabilities. 135 For instance, the preamble of the CRPD states "that disability results from the interaction between persons with impairments and attitudinal and environmental barriers that hinders their full and effective participation in society on an equal basis with others" 136 It also recognizes "difficult conditions faced by persons with disabilities who are subject to multiple or aggravated forms of discrimination on the basis of race, colour, sex, language, religion, political or other opinion, national, ethnic, indigenous or social origin, property, birth, age or other <http://www.un.org/disabilities/default.asp?id=17>. Also, in regard to Article 12 (4), Canada reserves the right not to subject all such measures to regular review by an independent authority, where such measures are already subject to review or appeal.…”
Section: United Nations Convention On the Rights Of Persons With Disamentioning
confidence: 99%
“…However, some lawyers felt that psychiatrists and other health care professionals were grappling with these issues in the diagnostic process to the best of their abilities, given the time constraints and lack of resources. 136 137 Accordingly, a few lawyers suggested that the culture within psychiatric institutions had to change in order to ensure that health care professionals have the time and resources to address these issues within their capacity assessments. 138 Lawyers agreed that language and communication barriers affected a client's ability to be found incapable vs. capable.…”
Section: A Line Must Be Drawn Between Rights Advice and Advocacy Becamentioning
confidence: 99%
“…"a group sharing cultural features different from those of larger society, including a shared language or dialect") addresses issues of core theoretical and empirical concern to the discipline of sociology [97]. Besides exploring dominant contemporary concepts of mental health and their effect on social relationships [98] this subject area also focuses on improving pathways in to mental healthcare for ethnic minority groups afflicted by mental and psychosocial disabilities [99]. With this in mind, it is perhaps unsurprising that culture plays a significant role in shaping the experience and expression of emotional distress and social problems.…”
Section: Ethno Cultural Communities and Mental Healthmentioning
confidence: 99%
“…The consensus is that poor access to mental healthcare can be associated with an increased utilization of the police and prison justice system, increased use of crisis and emergency care, increased hospitalization (involuntary), poorer outcomes, and an increased community burden of mental illness [99]. The picture is however complex and dependent on context.…”
Section: Ethno Cultural Communities and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation